\[\boxed{\text{311\ (311).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
Пояснение.
Решение.
\[1)\ y = (x + 10)^{2} - 16\]
\[( - 10; - 16) - вершина;\]
\[III\ четверть.\]
\[2)\ y = (x - 11)^{2} + 15\]
\[(11;15) - вершина;\]
\[I\ четверть.\]
\[3)\ y = (x + 15)^{2} + 4\]
\[( - 15;4) - вершина. + ;\]
\[II\ четверть.\]
\[4)\ y = (x - 11)^{2} - 9\]
\[(11;\ - 9) - вершина;\]
\[IV\ четверть.\]
\[\boxed{\text{311.}\text{\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ \left\{ \begin{matrix} 1 \leq x \leq 3\ \ \ \ \\ - 4 < y < 5 \\ \end{matrix} \right.\ \]
\[2)\ \left\{ \begin{matrix} x^{2} + y^{2} \geq 1\ \ \ \ \ \ \\ - 0,5 \leq y \leq 0,5 \\ \end{matrix} \right.\ \]